2023
DOI: 10.1101/2023.09.21.23295879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Tai Ji and/or Qigong on Patients with Stable Chronic Obstructive Pulmonary Disease A protocol for meta-analysis and systematic review

Hongliang Liu,
Ningchang Cheng

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a global health problem with high morbidity and mortality. Tai Ji and Qigong are traditional Chinese mediative movements, benefit COPD patient’s physical and mental health. Methods: We searched the following twelve databases Web of Science, EBSCO, Medline, EMBASE, Scopus, PubMed, PsycArticles, Psychology and Behavioral Sciences Collection, PsycInfo, CINAHL, Cochrane Library online and Clinical trials from inception to July 2023. Any RCTs managed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…All of the included trials described randomized allocation, and they were low risk in the fields of randomized allocation. Twelve studies were classified as having an unclear risk in the fields of allocation concealment [18][19][20][21][24][25][26][27][28][30][31][32] and one was high risk. [22] There was high risk of bias in the domain of blinding of participants and personnel, only 3 studies [23,29,33] used single-blind method, but no specific method of blinding was mentioned in these studies.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the included trials described randomized allocation, and they were low risk in the fields of randomized allocation. Twelve studies were classified as having an unclear risk in the fields of allocation concealment [18][19][20][21][24][25][26][27][28][30][31][32] and one was high risk. [22] There was high risk of bias in the domain of blinding of participants and personnel, only 3 studies [23,29,33] used single-blind method, but no specific method of blinding was mentioned in these studies.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Only five of them were shown to blind their outcome assessment. [21,[23][24][32][33] All trials reported methods with a low risk of incomplete outcome data and 38 studies were at low risk of bias. With regard to selective outcome reporting bias, 10 studies were determined as low risk and the remaining were determined as unclear risk.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations